A Case of Primary Hepatic Lymphoma and Related Literature Review. (14th June 2016) - Liu, Yonghua; Jiang, Jinhong; Wu, Qinli; Zhang, Qiaolei; Xu, Yehui; Qu, Zhigang; Ma, Guangli; Wang, Xiaoqiu; Wang, Xiaoli; Jin, Weimei; Fang, Bingmu
Abstract : Objective . Primary hepatic lymphoma is a rare disease. And the clinical manifestations of this disease are nonspecific. The objective of this paper is to improve clinicians' understanding of this disease. Methods . We analyzed the clinical characteristics of a case of primary hepatic lymphoma in association with hepatitis B virus infection and reviewed the literature. Conclusion . The clinical manifestations of primary hepatic lymphoma are nonspecific. And it is easily misdiagnosed. Postoperative radiotherapy of patients with early stage was previously speculated to achieve favorable improvement. The application of targeted therapeutic drugs, chemotherapy, or combined local radiotherapy has become the first-line treatment strategy.